Políticas económicas óptimas en el ciclo y en el desarrollo sustentable de América Latina - Granado, María José; Paz Terán, Corina María; Rios De Gonzalez, Liliana; Fridrij, Gabriel Amos; Olguín, Dana Sofía; Saracho, Omar Ariel; Formoso Requena, María Emilse; Costa, Santiago Federico; Zanellato, Giuliano (Universidad Nacional de Tucumán, 2025)
Poster